Validity of the WHO-recommended ARI case assessment in the diagnosis of pneumonia in children less than five presenting with cough and fever in a highly endemic area for malaria in the Philippines - Lupisan, Socorro P.
To determine the validity of WHO-recommended ARI case assessment protocol, specifically fast breathing, chest indrawing, inability to drink or cyanosis (WCAP) in the diagnosis of pneumonia in Filipino children 5 years old presenting with cough or difficult breathing and fever or history of fever in Palawan.Pneumonia is a leading cause of mortality among children 5. The WHO recommended ARI case assessment (WCAP) was validated and the recommended management strategy was observed to reduce mortality in children. A current concern is the possibility of pneumonia and malaria in a child presenting with cough or difficult breathing or fast breathing and fever in a malaria-endemic area in the Philippines. In the light of an integrated management, data on the validity of WCAP and the overlap of both diseases among children 5 in a malaria endemic area in the country will clarify assessment and treatment guidelines for the sick child 5 presenting with cough and fever.This was a cross-sectional study carried out in Palawan, a province in the Philippines which is highly endemic for malaria. WCAP (fast breathing, chest indrawing, inability to drink or cyanosis) was the tool evaluated and chest x-ray confirmed pneumonia was the gold standard used. Blood smear for malaria was done to determine co-infection. Children 5 years old from malaria-edemic areas in Palawan, consulting at the hospital and designated community health facilities for cough or difficult breathing and fever or history of fever during the last two days were enrolled consecutively. History and physical examination related to both diseases were obtained by trained health providers. Chest x-rays were read by an expert radiologist who was blind to the clinical presentation and assessment of all children. Blood films for malaria were validated by an RITM trained medical technologist.Data from 244 patients with evaluable chest x-rays and blood films for malaria were included in the analysis. Majority of the patients were from Puerto Princesa and were enrolled at the hospital. The prevalence rate of radiographic pneumonia in this population was 21. The prevalence of microscopy- confirmed malaria infection was 15.3. . Using polytomous logistic regression, fast breathing was an independent predictor or pnyemonia. It was observed to be as sensitive (62.7; 95 CI 48.1, 75.7) as in a local non-endemic area. Inclusion of chest indrawing, inability to drink and central cyanosis to fast breathing (WCAP) resulted in a higher sensitivity (78; 95 CI 63.7, 88.0) which was within the 95 confidence limits of the true value. This sensitivity is similar to those observed in malaria hyperendemic populations in Africa. Of the WCAP signs, fast breathing and fast breathing or chest indrawing would result in 55 and 53 cases appropriately treated and 37 and 39 of cases inappropriately given antibiotics, respectively. Fast breathing and/or chest indrawing would be six times more likely to come from patients with radiographic pneumonia. The overlap between both diseases was also low. The predictors of malaria infection included history of convulsions and pallor. Headache in an older child was strongly associated with malaria infection.Fast breathing and WCAP are senstive and useful tools for the diagnosis of pneumonia in children 5 years old presenting with cough or difficult breathing and fever in a malaria endemic area with transmission rate similar to Puerto Princesa area in the Philippines. The combination of fast breathing with chest indrawing strongly suggest pneumonia. Malaria infection should be suspected if these children also present with convulsion history, pallor or headache (if child is older). In the preparation of treatment guidelines for the integrated management of the sick child, these factors should be considered.